Paraneoplastic Neuropathies: What's New Since the 2004 Recommended Diagnostic Criteria - Zoccarato, Marco; Grisold, Wolfgang; Grisold, Anna; Poretto, Valentina; Boso, Federica; Giometto, Bruno (Frontiers in Neurology, 2021)
The diagnostic criteria published by the PNS (Paraneoplastic Neurological Syndromes) Euronetwork in 2004 provided a useful classification of PNS, including paraneoplastic neuropathies. Subacute sensory neuronopathy (SSN) was the most frequently observed peripheral PNS, whereas other forms of neuropathy, as sensory polyneuropathy, sensorimotor polyneuropathy, demyelinating neuropathies, autonomic neuropathies, and focal nerve or plexus lesions, were less frequent. At the time of publication, the main focus was on onconeural antibodies, but knowledge regarding the mechanisms has since expanded. The antibodies associated with PNS are commonly classified as onconeural (intracellular) and neuronal surface antibodies (NSAbs). Since 2004, the number of antibodies and the associated tumors has increased. Knowledge has grown on the mechanisms underlying the neuropathies observed in lymphoma, paraproteinemia, and multiple myeloma. Moreover, other unrevealed mechanisms underpin sensorimotor neuropathies and late-stage neuropathies, where patients in advanced stages of cancer - often associated with weight loss - experience some mild sensorimotor neuropathy, without concomitant use of neurotoxic drugs. The spectrum of paraneoplastic neuropathies has increased to encompass motor neuropathies, small fiber neuropathies, and autonomic and nerve hyperexcitability syndromes. In addition, also focal neuropathies, as cranial nerves, plexopathies, and mononeuropathies, are considered in some cases to be of paraneoplastic origin. A key differential diagnosis for paraneoplastic neuropathy, during the course of cancer disease (the rare occurrence of a PNS), is chemotherapy-induced peripheral neuropathy (CIPN). Today novel complications that also involve the peripheral nervous system are emerging from novel anti-cancer therapies, as targeted and immune checkpoint inhibitor (ICH) treatment. Therapeutic options are categorized into causal and symptomatic. Causal treatments anecdotally mention tumor removal. Immunomodulation is sometimes performed for immune-mediated conditions but is still far from constituting evidence. Symptomatic treatment must always be considered, consisting of both drug therapy (e.g., pain), and attempts to treat disability and neuropathic pain.